Pengembangan Media Pembelajaran Berbasis Website Materi Passing Bola Voli Sekolah Dasar - Martini, Ketut Pasek; Suwiwa, I Gede; Adnyana, I Komang Sukarata (Jurnal IKA, 2024)
This research aims to develop website-based learning media regarding volleyball passing for class V students at SD N 1 Sari Mekar. The type of research used in the research is development research with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The subject of this research were all V grade students at SD N 1 Sari Mekar. The instrument use is a 5 scale with quantitative descriptive data analysis techniques. Based on the research results, it was found that the percentage of content/learning material expert tests was 98% with very good qualifications, 97.1% for learning design expert tests had very good qualifications, 92% for learning media expert tests had very good qualifications, 82% for small group practicality test with very  practical qualifications, and the practicality test of a large group of 85% qualified verry practical. Based on the results of this research, website-based learning media regarding volleyball passing material for class V students at SD N 1 Sari Mekar is very suitable for elementary school (SD) students to use as a learning resource, so that it can improve learning achievement and learning quality